Carbon sequestration and soil fertility of tropical tree plantations and secondary forest established on degraded land - sang MinhPhan; Bonner Mark; Lamb David; Schmidt Susanne (Plant and Soil, 2013)
Purpose:Much tropical land requires rehabilitation but the capacity of reforestation with plantations or naturally regenerating secondary forests for overcoming soil degradation remains unclear. We hypothesised that desirable effects, including improved soil fertility and carbon sequestration, are achieved to a agreater extent in Acacia mangium plantations and secondary forests than in Eucalyptus urophylla plantations. Methods: We tested our hypothesis soil and climate gradients in Vietnam with linear mixed-effect models and other, comparing A. mangium and E. urophylla plantations, secondary forests showed a positive correlation between biomass production and desirable soils properties including increased soil carbon, nitrogen and phosphurus, and reduced bulk density. All plantations, but not secondary forests, caused increases in soil acidity. Eight-year old A. mangium plantations contained most carbon in biomass+soil, and secondary forests and pastures had similar a higher soil carbon. E. urophylla plantations had the lowest soil carbon status, raising doubt about their sequestration capacity in current 6-8 uear rotations. Conclusion: The study demonstrate that appropriate reforestation enhances soil fertility and promotes carbon sequestration on degraded tropical lands and that unmanaged secondary forests are effective at improving soil fertility and sequestering carbon at low cost.
Keywords: Aboveground biomass; Acacia mangium; Eucalyptus urophylla; Land rehabilitation; Land use; Soil restoration